2019
DOI: 10.1371/journal.pone.0224892
|View full text |Cite
|
Sign up to set email alerts
|

Blood metal levels and serum testosterone concentrations in male and female children and adolescents: NHANES 2011–2012

Abstract: Environmental exposure to metals is ubiquitous, but its relation to androgen hormone levels is not well understood, especially in children and adolescents. This study aimed to explore the relationship between blood metal concentrations (lead, cadmium, total mercury, selenium, and manganese) and serum total testosterone (TT) levels in 6–19-year-old children and adolescents in the National Health and Nutrition Examination Survey (NHANES) 2011–2012. Weighted multivariable linear regression models using NHANES sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…1 × 10 −10 -1.2 × 10 −8 M for free testosterone and ca. 2 × 10 −8 -5 × 10 −7 M for free estradiol [25,26] that seems to be incompatible with the K i values of 10 −5 -10 −4 M determined for the hormone action on CcO in our experiments. However, it is noted that steroid hormones are very lipophilic and partition from water to octanol with a coefficient of 10 3 -10 4 [27], so that their concentration in the mitochondrial membranes may be very much higher than in blood serum.…”
Section: Discussioncontrasting
confidence: 85%
“…1 × 10 −10 -1.2 × 10 −8 M for free testosterone and ca. 2 × 10 −8 -5 × 10 −7 M for free estradiol [25,26] that seems to be incompatible with the K i values of 10 −5 -10 −4 M determined for the hormone action on CcO in our experiments. However, it is noted that steroid hormones are very lipophilic and partition from water to octanol with a coefficient of 10 3 -10 4 [27], so that their concentration in the mitochondrial membranes may be very much higher than in blood serum.…”
Section: Discussioncontrasting
confidence: 85%
“…In a study carried out to evaluate the relationship between blood metal concentrations and testosterone levels in the USA, children and adolescents' concentrations of lead, cadmium, mercury, and selenium in blood, as well as serum testosterone levels, were determined [102]. Although no significant association between blood lead and total testosterone (TT) was observed, the concentrations of TT were significantly higher for girls in the fourth quartile compared to those in the first quartile.…”
Section: Lead Exposure and Children's Reproductive Systemmentioning
confidence: 99%
“…A very recent study on 133 boys aged 15-17 reported that combined exposure to toxic metals was associated with increased testosterone and LH [121]. A positive association of heavy metals with total testosterone levels was also observed in the NHANES cohort of adolescents [122], suggesting a compensatory mechanism possibly due to inefficient recognition of testosterone on its receptor, as confirmed by elevated LH levels. A study on 111 adolescents (age [12][13][14] with increased urinary cadmium levels reported delayed onset of puberty, reduced testicular volume, but reduced testosterone and LH levels, probably due to a direct toxic effect of cadmium on the Leydig cells [123].…”
Section: Effects Of Endocrine Disruptorsmentioning
confidence: 87%